Pengembangan Pop-Up Book Video Digital Tema 7 Subtema 1 Pembelajaran 1 Kelas IV - Imas Maulidiyah; Muhammad Nuruddin (IJPSE : Indonesian Journal of Primary Science Education, 2023)
The learning process that only utilizes media that is often used by students, makes students feel bored and bored so that there is a need for learning media that follows the modern era and can make it easier for students to learn both guided and individually. The goals to be achieved in this research are (1) to describe the expansion process of pop-up book media. on theme 7 sub-theme 1 learning 1, (2) understanding the quality of media development of digital video-oriented pop-up book theme 7 sub-theme 1 learning 1, and ( 3) understand the results of the implementation of digital video-oriented pop-up book media on the theme of 7 sub-themes 1 learning 1. This research adopts an R&D research (research and development) type using the Addie model, which has five stages of development: analysis, design, development, implementation, and evaluation. The results of the research conducted include the appropriate and adequate digital video-oriented pop-up book media to be used as learning media. According to the media expert's validation value, 95% is very valid, while the material expert's validation is 81.6% valid. In the normality test and hypothesis testing, it is significant so that H0 is checked and Ha is accepted. The results of the implementation of the pop-up book media through observation are 98.3% while the average percentage of student response data questionnaires is 90% which is considered feasible and valid to use. Keywords: Pop-up book, digital video, theme 7 sub-theme 1 learning 1